KONSEP MASYARAKAT MULTIKUTURAL DI INDONESIA DALAM PERSPEKTIF ISLAM - Faelasup (Madani : Journal of Social Sciences and Social Science Education, 2024)
Research on the concept of a multicultural society is motivated by conditions that often occur, namely, social fights, political fights, culture, and even economy, all of which greatly influence the unity and integrity of the nation. From this background, the researcher tries to conduct research, whose research results can be used as an alternative study of people's lives. This type of research is liberary research (literature study), the data can be taken from actual news from newspapers, literature books, and journals. The analysis technique is to study the theory of references, and also to search the Al-Quran and Hadith books, as well as other relevant books. The results and discussion included 1) the concept of a multicultural society that is very appropriate to be applied in Indonesia, because it is in accordance with the conditions of Indonesia which have diversity, be it race, ethnicity, culture and religion. 2) Nadlatul Ulama (NU) as a civil society has fought for this multicultural concept through NU's formal education channels, education in Islamic boarding schools, and recitation of fathers and recitation of women in society. 3) The Islamic perspective on the concept of a multicultural society is very positive, meaning that Islam provides full support and legally there is no imbalance, even so much is revealed in Islamic law either through the Al-Qur'an or Al-Hadith.